Carbon microspheres as well as preparation method and application thereof

By controlling the ratio of resin, catalyst and solvent and heating parameters through suspension polymerization, carbon microspheres with complex structures are formed, which solves the problems of long production cycle and single structure in existing technologies, achieves high specific surface area and improved utilization of active sites, and is suitable for fields such as supercapacitors.

CN120717447AActive Publication Date: 2025-09-30INST OF METAL RESEARCH - CHINESE ACAD OF SCI
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202511133862.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-14
Publication Date
2025-09-30
Estimated Expiration
2045-08-14

AI Technical Summary

Technical Problem

The existing micron-sized carbon sphere preparation process has the problems of long production cycle, high energy consumption and single structure, resulting in low specific surface area and low utilization of active sites.

Method used

The suspension polymerization method is used to control the ratio of resin, acid catalyst and alcohol solvent and the heating parameters to form micron-sized droplets with controllable particle size. The Marconi effect is used to form carbon microspheres with complex internal structures in a short period of time, which are then carbonized at high temperature.

Benefits of technology

The rapid prototyping of carbon microspheres with complex internal structures is achieved, which increases the specific surface area and active site utilization, making them suitable for applications such as supercapacitors.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120717447A_ABST
    Figure CN120717447A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of carbon microsphere preparation, and particularly relates to a carbon microsphere as well as a preparation method and application thereof. The preparation method of the carbon microspheres comprises the following steps: (1) dissolving resin and an acid catalyst in an alcohol solvent to form a precursor solution; (2) adding the precursor solution into the oily continuous phase, and emulsifying to prepare an emulsion; (3) heating and curing the emulsion to form resin microspheres; and (4) separating, cleaning, drying and carbonizing the resin microspheres to obtain the carbon microspheres. The key point of the invention lies in that the curing time of the resin microspheres is obviously shortened by selecting a specific catalyst; meanwhile, the particle size and the microstructure of the obtained carbon microspheres can be effectively regulated and controlled by accurately controlling the emulsifying rotating speed and the curing reaction conditions. The prepared carbon microspheres can be used as an electrode active material of a supercapacitor, and the specific capacitance of an electrode prepared by using the carbon microspheres as the electrode active material can reach 200-300 F / g in a 6M KOH aqueous solution.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of carbon microsphere preparation, and in particular relates to carbon microspheres, a preparation method and application thereof. Background Art

[0002] Carbon-based functional materials have shown important application value in various fields due to their unique physical and chemical properties. Among them, carbon spheres, as an extremely important carbon material, have high specific surface area, excellent conductivity, good structural stability and fluidity, which makes them have broad application prospects in energy storage (such as supercapacitors, lithium-sulfur batteries, sodium-ion batteries, silicon-carbon negative electrodes), heterogeneous catalytic reaction systems, gas adsorption and separation, and electromagnetic wave absorption materials.

[0003] The current mainstream preparation technologies for carbon spheres include: (1) hydrothermal synthesis: carbon spheres are formed through the self-assembly of precursors such as sugars; (2) template-directed synthesis: the microsphere structure is regulated by using hard templates such as silica or soft templates such as surfactants; (3) spray drying: precursor microspheres are formed by rapid evaporation of solvents; and (4) suspension polymerization: microsphere morphology is constructed based on the oil-water interface. Although the above methods are relatively mature in the preparation of nanoscale carbon spheres, in practical applications, micron-scale carbon spheres are more popular due to their superior solid-liquid separation performance and processing adaptability.

[0004] Among existing processes for preparing micron-sized carbon spheres (carbon microspheres), suspension polymerization is widely used due to its simplicity. This method typically involves dispersing a precursor solution in a continuous phase medium to form a stable emulsion. This is followed by a prolonged heat curing process (10–24 h) to stabilize the microsphere structure, followed by high-temperature carbonization to obtain the carbon microspheres. However, this lengthy curing process results in extended production cycles and increased energy consumption, significantly hindering the economic viability of commercial production. Furthermore, existing processes struggle to overcome the limitations of a single microsphere structure, resulting in products that are mostly solid or hollow. These two structures result in low specific surface area and a single pore structure (mostly micropores), leading to low active site utilization and slow mass transfer efficiency. An effective approach to address this issue is to construct complex internal structures within the carbon microspheres (e.g., porous, network-like, multi-shell, or core-shell structures). These complex internal structures significantly increase the specific surface area of ​​the microspheres and often possess abundant micropores and mesopores, effectively enhancing active site utilization and mass transfer efficiency, which plays a key role in improving the performance of the carbon microspheres. Therefore, it is of great significance to develop a preparation technology for carbon microspheres with rapid prototyping characteristics and complex internal structures. Summary of the Invention

[0005] The present invention aims to provide carbon microspheres, their preparation method, and application. Using commercially available resins as raw materials, organic or inorganic acids as catalysts, and alcohols as organic solvents, the invention prepares carbon microspheres with varying microscopic morphologies and particle sizes by controlling parameters such as the mixing ratio, curing temperature, and carbonization temperature. This invention addresses the problems of the current suspension polymerization method, which suffers from long curing cycles and a single carbon sphere structure. To achieve the above objectives, the carbon microsphere preparation method of the present invention comprises the following steps:

[0006] (1) Preparation of precursor solution: dissolve the resin and acidic catalyst in an alcohol solvent to obtain a precursor solution; the mass ratio of the resin to the acidic catalyst is 200:1~1:1; the mass ratio of the alcohol solvent to the resin is 10:1~1:5;

[0007] (2) Emulsion preparation: adding the precursor solution obtained in step (1) to the oily continuous phase, emulsifying at a stirring speed of 3000-20000 r / min, preferably 4000-15000 r / min; emulsifying time 1-30 min, preferably 10-30 min; preparing an emulsion;

[0008] The mass ratio of the oily continuous phase to the precursor solution is 30:1 to 1:1, preferably 10:1 to 5:1;

[0009] (3) Resin curing: heating the emulsion obtained in step (2) at a temperature of 70 to 180° C. for 5 min to 1 h, preferably 10 to 40 min; the resin in the emulsion is cured into resin microspheres;

[0010] (4) Solid-liquid separation;

[0011] (5) Drying the resin microspheres: washing and drying the solid product after solid-liquid separation in step (4) to obtain dry resin microspheres; the drying temperature is 60-200°C, preferably 100-120°C; the drying time is 30 min-6 h, preferably 1-2 h;

[0012] (6) High-temperature carbonization: The dry resin microspheres obtained in step (5) are placed in a vacuum or inert atmosphere for high-temperature carbonization, wherein the carbonization temperature is 500-1500°C, preferably 600-1000°C; the carbonization heating rate is 1-10°C / min, preferably 2-6°C / min; the carbonization holding time is 1-10 h, preferably 2-4 h; and finally, a carbon microsphere product is obtained.

[0013] Furthermore, the resin in step (1) is one or more of melamine-formaldehyde resin, phosphorus-modified melamine-formaldehyde resin, boron-modified melamine-formaldehyde resin, sulfur-modified melamine-formaldehyde resin, phenolic resin, boron-modified phenolic resin, silicon-modified phenolic resin, silicon-boron-modified phenolic resin and chitosan-modified phenolic resin;

[0014] The acidic catalyst is one or more of formic acid, acetic acid, benzoic acid, hydrochloric acid, terephthalic acid, p-hydroxybenzenesulfonic acid, p-toluenesulfonic acid, p-hydroxybenzoic acid and p-toluic acid;

[0015] The alcohol solvent is one or more of ethylene glycol, glycerol, isopropyl alcohol and n-propyl alcohol.

[0016] Furthermore, the oily continuous phase in step (2) is one or more of dimethyl silicone oil, phenyl methyl silicone oil, epoxy silicone oil, and industrial white oil.

[0017] Furthermore, the cleaning solution in step (5) is one or more of solvent oil, benzene, xylene and kerosene.

[0018] Furthermore, the inert atmosphere in step (6) is one or both of nitrogen and argon, with a gas flow rate of 1 to 10 L / min, preferably 2 to 5 L / min; and the vacuum condition is a vacuum degree ≤ 0.1 kPa.

[0019] The carbon microspheres prepared by the method for preparing carbon microspheres of the present invention have a particle diameter of 1 to 30 μm and a specific surface area of ​​300 to 700 m 2 / g; A variety of micromorphologies can be formed by controlling the curing temperature and the ratio of resin, acid catalyst and alcohol solvent:

[0020] When the ratio of resin to acid catalyst is 30:1~10:1, the ratio of alcohol solvent to resin is 3:1~1:2, and the curing temperature is 70~140℃, the carbon microspheres have a shell-free aerogel structure;

[0021] When the ratio of resin to acid catalyst is 9:1-6:1, the ratio of alcohol solvent to resin is 3:1-1:2, and the curing temperature is 70-140 °C, the carbon microspheres are porous shell-encapsulated aerogel structures.

[0022] When the ratio of resin to acid catalyst is 5:1-3:1, the ratio of alcohol solvent to resin is 3:1-1:2, and the curing temperature is 70-160 °C, the carbon microspheres are dense shell-encapsulated aerogel structures.

[0023] When the ratio of resin to acid catalyst is 2:1~1:1, the ratio of alcohol solvent to resin is 10:1~1:2, and the curing temperature is 70~180℃, the carbon microspheres have a hollow dense shell structure.

[0024] When the ratio of resin to acid catalyst is 30:1~6:1, the ratio of alcohol solvent to resin is 3:1~1:2, and the curing temperature is 160~180℃, the carbon microspheres have an aerogel shell-hollow structure;

[0025] When the ratio of resin to acid catalyst is 200:1~1:1, the ratio of alcohol solvent to resin is 1:3~1:5, and the curing temperature is 70~180 ℃, the carbon microspheres have a solid structure.

[0026] The invention discloses an application of carbon microspheres as electrode active materials in supercapacitors. The electrode prepared by using the carbon microspheres as the electrode active material has a specific capacitance of 200-300 F / g in a 6M KOH aqueous solution.

[0027] The present invention provides a rapid, low-cost method for preparing carbon microspheres with controllable morphology. Its core design concept involves using a suspension polymerization method to uniformly disperse a precursor solution in an oil-phase continuous medium to form micron-sized droplets (the droplet diameter can be controlled by the speed of the emulsifier). Subsequently, under the catalytic action of high temperature and an acidic catalyst, these precursor droplets undergo phase separation in a very short time to form sol particles. Due to the different temperatures between the surface and core of the precursor droplets, the resulting temperature gradient leads to uneven tension across the surface of the sol particles, producing a Marconi effect. The sol particles gradually migrate toward the surface of the precursor droplets, continuously fusing to form a shell. When the temperature gradient disappears, the sol particles that have not fully migrated to the surface undergo a gelation reaction, forming an internal three-dimensional network structure. Therefore, by controlling the heating parameters and raw material ratio, the microspheres can be rapidly solidified and their morphology can be adjusted according to actual needs. Finally, carbon microspheres are obtained through high-temperature carbonization. This method has low raw material costs, a simple and efficient process, and a short preparation cycle, making it potentially suitable for large-scale commercial production.

[0028] The advantages and beneficial effects of the present invention are as follows:

[0029] 1. The key to this invention is that by selecting a specific catalyst, the curing time of the resin microspheres is significantly shortened. At the same time, by precisely controlling the emulsification speed and curing reaction conditions, the particle size and microscopic morphology of the obtained carbon microspheres can be effectively regulated.

[0030] 2. The present invention can precisely induce and control the formation and evolution of the internal microstructure of the resin microspheres during the curing process by systematically regulating key process parameters, thereby flexibly and adjustably achieving diversified customization of the final morphology and structure of the carbon microspheres.

[0031] 3. The present invention uses commercially available resins as raw materials, making the method applicable to a wide variety of resins and highly universal. Furthermore, compared to traditional processes for preparing carbon spheres using monomer synthesis, this method has lower raw material costs and a shorter production cycle.

[0032] 4. The carbon microspheres prepared by the present invention have a complex internal structure. Compared with hollow or solid carbon spheres of the same particle size, they have a higher specific surface area, lighter weight, greater specific strength, and abundant mesopores and micropores, which can improve the utilization rate of active sites and material transfer efficiency.

[0033] 5. The carbon microspheres prepared in the present invention have a particle diameter of 1-30 μm and a specific surface area of ​​about 300-700 m 2 / g, and the electrode prepared using the carbon microspheres as the active material of the supercapacitor electrode has a specific capacitance of 200~300 F / g in 6M KOH aqueous solution. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 Micromorphology and electrochemical performance of the porous shell-coated aerogel-structured carbon microspheres prepared in Example 1: (a) Scanning electron microscope macrograph; (b) Scanning electron microscope internal structure photograph; (c) Nitrogen isothermal adsorption-desorption curve; (d) Constant current charge-discharge curve;

[0035] Figure 2 Micromorphology and electrochemical performance of the dense shell-coated aerogel-structured carbon microspheres prepared in Example 2: (a) Scanning electron microscope macrograph; (b) Scanning electron microscope internal structure photograph; (c) Nitrogen isothermal adsorption-desorption curve; (d) Constant current charge-discharge curve;

[0036] Figure 3 Micromorphology and electrochemical performance of the aerogel shell-hollow structure carbon microspheres prepared in Example 3: (a) Scanning electron microscope macrograph; (b) Scanning electron microscope internal structure photograph; (c) Nitrogen isothermal adsorption-desorption curve; (d) Constant current charge-discharge curve;

[0037] Figure 4 Micromorphology and electrochemical performance of the shell-free aerogel-structured carbon microspheres prepared in Example 4: (a) Scanning electron microscope macrograph; (b) Scanning electron microscope internal structure photograph; (c) Nitrogen isothermal adsorption / desorption curve; (d) Constant current charge / discharge curve;

[0038] Figure 5 This is a scanning electron microscope photograph of the solid structure carbon microspheres prepared in Example 5;

[0039] Figure 6 This is a scanning electron microscope photograph of the hollow dense shell carbon microspheres prepared in Example 6;

[0040] Figure 7 This is a scanning electron microscope photograph of carbon particles prepared in Comparative Example 1;

[0041] Figure 8This is a scanning electron microscope photograph of the carbon block prepared in Comparative Example 2. DETAILED DESCRIPTION

[0042] In order to further understand the present invention, the present invention is described below in conjunction with examples, but the examples are only for further elaboration of the characteristics and advantages of the present invention, rather than for limitation of the technical solutions of the present invention.

[0043] Example 1

[0044] In this embodiment, the preparation method of carbon microspheres is as follows:

[0045] (1) Weigh 100 g of commercially available phenolic resin and 15 g of acetic acid and add them to 300 g of ethylene glycol. Stir continuously at room temperature until the phenolic resin and acetic acid are completely dissolved to obtain a homogeneous and transparent precursor solution.

[0046] (2) Weigh 200 g of the precursor solution and add it to 2000 g of 100# industrial white oil (purchased from Hongtai Petrochemical Co., Ltd.). Emulsify the mixture at room temperature using a high-speed emulsifier at 6000 r / min for 10 min to obtain a stable white alcohol-in-oil emulsion.

[0047] (3) The resulting white emulsion was transferred to a reaction vessel, heated to 100 °C, and kept at this temperature for 10 min. The white emulsion was observed to transform into a pink suspension, indicating that the phenolic resin microspheres were cured.

[0048] (4) The pink suspension was filtered and the solid product obtained was collected. The solid product was washed three times with 120# solvent oil (purchased from Shandong Juxing Chemical Co., Ltd.) to fully remove the residual industrial white oil.

[0049] (5) The cleaned solid product was placed in an oven at 100 °C and dried for 1 h to obtain dry phenolic resin microspheres.

[0050] (6) The dried phenolic resin microspheres were placed in a tube furnace and subjected to high-temperature carbonization treatment in a vacuum environment (vacuum degree 0.05 kPa). The carbonization temperature was 1000 °C, the carbonization holding time was 2 h, and the heating rate was 5 °C / min. After carbonization, the microspheres were cooled to room temperature in a vacuum environment to obtain carbon microspheres.

[0051] Electrode preparation:

[0052] (1) Weigh carbon microspheres, carbon black conductive agent, and polytetrafluoroethylene binder in a mass ratio of 8:1:1. After mixing the three evenly, add anhydrous ethanol as a dispersion medium and continue stirring until a uniform black slurry with good fluidity is formed.

[0053] (2) The obtained black slurry was evenly coated on the surface of the nickel foam collector, and then the coated nickel foam collector was placed in an oven at 100°C for 12 hours to completely remove the ethanol solvent to obtain the nickel foam electrode. The surface loading of the active material (carbon microspheres) on the nickel foam electrode was controlled to be about 1 mg / cm 2 .

[0054] (3) The dried nickel foam electrode was compacted using a tablet press. The tablet press pressure was set to 15 MPa and the tablet pressing time was 30 s.

[0055] Electrochemical performance characterization:

[0056] The compacted nickel foam electrode (electrode area: 1 cm 2 ) as the working electrode in a three-electrode test system (Hg / HgO as the reference electrode and a platinum electrode as the counter electrode), using 6 M KOH aqueous solution as the electrolyte. The test voltage window was set between -1.0 V and 0 V (vs. Hg / HgO).

[0057] Figure 1 (a) and (b) are scanning electron microscope images of the carbon microspheres prepared in this example. The images show that the carbon microspheres exhibit a porous shell-encapsulated aerogel structure: the aerogel internally exhibits a three-dimensional nanostructured network with particle sizes of 30-40 nm and pores of 10-50 nm; the outer layer is surrounded by a porous shell with pores of 10-20 nm and a thickness of approximately 100 nm. Statistical results indicate that the average particle size of the carbon microspheres is approximately 5 μm (with a particle size range of 2-8 μm). Figure 1 (c) is the nitrogen isothermal adsorption-desorption curve of the carbon microspheres in this example. According to the Brunauer-Emmett-Teller (BET) model, the specific surface area is 592 m 2 / g. Figure 1 (d) shows the galvanostatic charge-discharge curves of the carbon microspheres of this example at different current densities. Calculated according to the formula: specific capacitance = (discharge current × discharge time) / (voltage window), the specific capacitance at a current density of 0.2 A / g is 315 F / g.

[0058] Example 2

[0059] In this embodiment, the preparation method of carbon microspheres is as follows:

[0060] (1) Weigh 150 g of commercially available phenolic resin and 40 g of p-toluenesulfonic acid and add them to 300 g of ethylene glycol. Stir continuously at room temperature until the phenolic resin and p-toluenesulfonic acid are completely dissolved to obtain a homogeneous and transparent precursor solution.

[0061] (2) Weigh 200 g of the precursor solution and add it to 2000 g of dimethyl silicone oil. Emulsify the mixture at room temperature using a high-speed emulsifier at 4000 r / min for 10 min to obtain a stable white oil-in-alcohol emulsion.

[0062] (3) The obtained white emulsion was transferred to a reaction vessel, heated to 150 °C, and kept at this temperature for 30 min. The white emulsion was observed to transform into a pink suspension, indicating that the phenolic resin microspheres were cured.

[0063] (4) The pink suspension was filtered and the solid product was collected. The solid product was washed three times with 120# solvent oil to fully remove the residual dimethyl silicone oil.

[0064] (5) The cleaned solid product was placed in an oven at 100 °C and dried for 1 h to obtain dry phenolic resin microspheres.

[0065] (6) The dried phenolic resin microspheres were placed in a tube furnace and subjected to high-temperature carbonization treatment in an argon atmosphere. The carbonization temperature was 800 °C, the carbonization holding time was 2 h, the heating rate was 5 °C / min, and the argon gas flow rate was 2 L / min. After carbonization, the microspheres were cooled to room temperature in an argon atmosphere to obtain carbon microspheres.

[0066] Electrode preparation:

[0067] (1) Weigh carbon microspheres, carbon black conductive agent, and polytetrafluoroethylene binder in a mass ratio of 8:1:1. After mixing the three evenly, add anhydrous ethanol as a dispersion medium and continue stirring until a uniform black slurry with good fluidity is formed.

[0068] (2) The obtained black slurry was evenly coated on the surface of the nickel foam collector, and then the coated nickel foam collector was placed in an oven at 100°C for 12 hours to completely remove the ethanol solvent to obtain the nickel foam electrode. The surface loading of the active material (carbon microspheres) on the nickel foam electrode was controlled to be about 1 mg / cm 2 .

[0069] (3) The dried nickel foam electrode was compacted using a tablet press. The tablet press pressure was set to 15 MPa and the tablet pressing time was 30 s.

[0070] Electrochemical performance test:

[0071] The compacted nickel foam electrode (electrode area: 1 cm 2) as the working electrode in a three-electrode test system (Hg / HgO as the reference electrode and a platinum electrode as the counter electrode), using 6 M KOH aqueous solution as the electrolyte. The test voltage window was set between -1.0 V and 0 V (vs. Hg / HgO).

[0072] Figure 2 (a) and (b) are scanning electron microscope images of the carbon microspheres prepared in this example. The images show that the carbon microspheres exhibit a dense shell-encapsulated aerogel structure: the inner aerogel comprises a three-dimensional nanostructured network with particle sizes ranging from 100 to 150 nm and pores ranging from 30 to 90 nm. The outer layer is covered by a dense shell approximately 200 nm thick and with pores less than 2 nm in diameter. Statistical results indicate that the average particle size of the carbon microspheres is approximately 8 μm (with a particle size range of 3-10 μm). Figure 2 (c) is the nitrogen isothermal adsorption-desorption curve of the carbon microspheres in this example. According to the Brunauer-Emmett-Teller (BET) model, the specific surface area is 678 m 2 / g. Figure 2 (d) shows the galvanostatic charge-discharge curves of the carbon microspheres of this example at different current densities. Calculated according to the formula: specific capacitance = (discharge current × discharge time) / (voltage window), the specific capacitance at a current density of 0.2 A / g is 321 F / g.

[0073] Example 3

[0074] In this embodiment, the preparation method of carbon microspheres is as follows:

[0075] (1) Weigh 200 g of commercially available boron phenolic resin and 10 g of p-hydroxybenzenesulfonic acid and add them to 200 g of propylene glycol. Stir continuously at room temperature until the boron phenolic resin and p-hydroxybenzenesulfonic acid are completely dissolved to obtain a uniform and transparent precursor solution.

[0076] (2) Weigh 300 g of the precursor solution and add it to 2000 g of epoxy-terminated silicone oil. Emulsify the mixture at room temperature using a high-speed emulsifier at 8000 r / min for 30 min to obtain a stable white alcohol-in-oil emulsion.

[0077] (3) The obtained white emulsion was transferred to a reaction vessel, heated to 180 °C, and kept at this temperature for 10 min. The white emulsion was observed to transform into a pink suspension, indicating that the boron phenolic resin microspheres were cured.

[0078] (4) The pink suspension was filtered and the solid product was collected. The solid product was washed three times with acetone to fully remove the residual end-epoxy silicone oil.

[0079] (5) The washed solid product was placed in an oven at 100 °C and dried for 1 h to obtain dry boron phenolic resin microspheres.

[0080] (6) The dried boron phenolic resin microspheres were placed in a tube furnace and subjected to high-temperature carbonization treatment in an argon atmosphere. The carbonization temperature was 1200 °C, the carbonization holding time was 4 h, the heating rate was 3 °C / min, and the argon gas flow rate was 5 L / min. After carbonization, the microspheres were cooled to room temperature in an argon atmosphere to obtain carbon microspheres.

[0081] Electrode preparation:

[0082] (1) Weigh carbon microspheres, carbon black conductive agent, and polytetrafluoroethylene binder in a mass ratio of 8:1:1. After mixing the three evenly, add anhydrous ethanol as a dispersion medium and continue stirring until a uniform black slurry with good fluidity is formed.

[0083] (2) The obtained black slurry was evenly coated on the surface of the nickel foam collector, and then the coated nickel foam collector was placed in an oven at 100°C for 12 hours to completely remove the ethanol solvent to obtain the nickel foam electrode. The surface loading of the active material (carbon microspheres) on the nickel foam electrode was controlled to be about 1 mg / cm 2 .

[0084] (3) The dried nickel foam electrode was compacted using a tablet press. The tablet press pressure was set to 15 MPa and the tablet pressing time was 30 s.

[0085] Electrochemical performance test:

[0086] The compacted nickel foam electrode (electrode area: 1 cm 2 ) as the working electrode in a three-electrode test system (Hg / HgO as the reference electrode and a platinum electrode as the counter electrode), using 6 M KOH aqueous solution as the electrolyte. The test voltage window was set between -1.0 V and 0 V (vs. Hg / HgO).

[0087] Figure 3 (a) and (b) are scanning electron micrographs of the carbon microspheres prepared in this example. The images show an aerogel shell-hollow structure, with a shell thickness of approximately 700 nm, shell particles ranging from 110 to 160 nm, and pores approximately 40 nm in diameter. Statistical results indicate that the average particle size of the carbon microspheres is approximately 4 μm (with a particle size range of 2 to 6 μm). Figure 3 (c) is the nitrogen isothermal adsorption-desorption curve of the carbon microspheres in this example. According to the Brunauer-Emmett-Teller (BET) model, the specific surface area is 500 m2 / g. Figure 3 (d) shows the galvanostatic charge-discharge curves of the carbon microspheres of this example at different current densities. Calculated according to the formula: specific capacitance = (discharge current × discharge time) / (voltage window), the specific capacitance at a current density of 0.2 A / g is 285 F / g.

[0088] Example 4

[0089] In this embodiment, the preparation method of carbon microspheres is as follows:

[0090] (1) Weigh 200 g of commercially available melamine-formaldehyde resin and 15 g of benzoic acid and add them to 400 g of ethylene glycol. Stir continuously at room temperature until the melamine-formaldehyde resin and benzoic acid are completely dissolved to obtain a homogeneous and transparent precursor solution.

[0091] (2) Weigh 200 g of the precursor solution and add it to 2000 g of dimethyl silicone oil. Emulsify the mixture at room temperature using a high-speed emulsifier at a speed of 10,000 r / min for 20 min to obtain a stable white oil-in-alcohol emulsion.

[0092] (3) The resulting white emulsion was transferred to a reaction vessel, heated to 120 °C, and kept at this temperature for 20 min. The white emulsion was observed to transform into a white suspension, indicating that the melamine-formaldehyde resin microspheres were cured.

[0093] (4) The white suspension was filtered and separated, and the solid product obtained by filtration was collected. The solid product was washed with acetone for multiple times to fully remove the residual dimethyl silicone oil.

[0094] (5) The washed solid product was placed in an oven at 100 °C and dried for 1 h to obtain dry melamine-formaldehyde resin microspheres.

[0095] (6) The dried melamine-formaldehyde resin microspheres were placed in a tube furnace and subjected to high-temperature carbonization treatment under vacuum (vacuum degree 0.1 kPa). The carbonization temperature was 1000 °C, the carbonization holding time was 1 h, and the heating rate was 10 °C / min. After carbonization, the microspheres were cooled to room temperature under vacuum to obtain carbon microspheres.

[0096] Electrode preparation:

[0097] (1) Weigh carbon microspheres, carbon black conductive agent, and polytetrafluoroethylene binder in a mass ratio of 8:1:1. After mixing the three evenly, add anhydrous ethanol as a dispersion medium and continue stirring until a uniform black slurry with good fluidity is formed.

[0098] (2) The obtained black slurry was evenly coated on the surface of the nickel foam collector, and then the coated nickel foam collector was placed in an oven at 100°C for 12 hours to completely remove the ethanol solvent to obtain the nickel foam electrode. The surface loading of the active material (carbon microspheres) on the nickel foam electrode was controlled to be about 1 mg / cm 2 .

[0099] (3) The dried nickel foam electrode was compacted using a tablet press. The tablet press pressure was set to 15 MPa and the tablet pressing time was 30 s.

[0100] Electrochemical performance test:

[0101] The compacted nickel foam electrode (electrode area: 1 cm 2 ) as the working electrode in a three-electrode test system (Hg / HgO as the reference electrode and a platinum electrode as the counter electrode), using 6 M KOH aqueous solution as the electrolyte. The test voltage window was set between -1.0 V and 0 V (vs. Hg / HgO).

[0102] Figure 4 (a) and (b) are scanning electron microscope images of the carbon microspheres prepared in this example. The images show that the carbon microspheres have a shell-less aerogel structure with particle sizes ranging from 20 to 40 nm and pore sizes of approximately 10 to 40 nm. Statistical results indicate that the average particle size of the carbon microspheres is approximately 3 μm (with a particle size range of 1 to 6 μm). Figure 4 (c) is the nitrogen isothermal adsorption-desorption curve of the carbon microspheres in this example. According to the Brunauer-Emmett-Teller (BET) model, the specific surface area is 561 m 2 / g. Figure 4 (d) shows the galvanostatic charge-discharge curves of the carbon microspheres of this example at different current densities. Calculated according to the formula: specific capacitance = (discharge current × discharge time) / (voltage window), the specific capacitance at a current density of 0.2 A / g is 232 F / g.

[0103] Example 5

[0104] In this embodiment, the preparation method of carbon microspheres is as follows:

[0105] (1) Weigh 180 g of commercially available phenolic resin and 24 g of p-hydroxybenzenesulfonic acid and add them to 60 g of ethylene glycol. Stir continuously at room temperature until the phenolic resin and p-hydroxybenzenesulfonic acid are completely dissolved to obtain a uniform and transparent precursor solution.

[0106] (2) Weigh 100 g of the precursor solution and add it to 2000 g of phenylmethyl silicone oil. Emulsify the mixture at room temperature using a high-speed emulsifier at 6000 r / min for 20 min to obtain a stable white oil-in-alcohol emulsion.

[0107] (3) The resulting white emulsion was transferred to a reaction vessel, heated to 180 °C, and kept at this temperature for 25 min. The white emulsion was observed to transform into a pink suspension, indicating that the phenolic resin microspheres were cured.

[0108] (4) The pink suspension was filtered and the solid product was collected. The solid product was washed three times with acetone to fully remove the residual phenylmethyl silicone oil.

[0109] (5) The washed solid product was placed in an oven at 120 °C and dried for 5 h to obtain dry phenolic resin microspheres.

[0110] (6) The dried phenolic resin microspheres were placed in a tube furnace and subjected to high-temperature carbonization treatment under vacuum (vacuum degree 0.1 kPa). The carbonization temperature was 800 °C, the carbonization holding time was 2 h, and the heating rate was 10 °C / min. After carbonization, the microspheres were cooled to room temperature under vacuum to obtain carbon microspheres.

[0111] Figure 5 This is a scanning electron microscope image of the carbon microspheres prepared in this example. The image shows that the carbon microspheres are solid, with no apparent pores on the surface and a dense, solid interior. Statistical results indicate that the average particle size of the carbon microspheres is approximately 4 μm (with a particle size range of 2 to 8 μm).

[0112] Example 6

[0113] In this embodiment, the preparation method of carbon microspheres is as follows:

[0114] (1) Weigh 180 g of commercially available phenolic resin and 90 g of p-hydroxybenzoic acid and add them to 360 g of ethylene glycol. Stir continuously at room temperature until the phenolic resin and p-hydroxybenzoic acid are completely dissolved to obtain a uniform and transparent precursor solution.

[0115] (2) Weigh 100 g of the precursor solution and add it to 2000 g of phenylmethyl silicone oil. Emulsify the mixture at room temperature using a high-speed emulsifier at 6000 r / min for 20 min to obtain a stable white oil-in-alcohol emulsion.

[0116] (3) The resulting white emulsion was transferred to a reaction vessel, heated to 160 °C, and kept at this temperature for 25 min. The white emulsion was observed to transform into a pink suspension, indicating that the phenolic resin microspheres were cured.

[0117] (4) The pink suspension was filtered and the solid product was collected. The solid product was washed three times with acetone to fully remove the residual phenylmethyl silicone oil.

[0118] (5) The washed solid product was placed in an oven at 120 °C and dried for 5 h to obtain dry phenolic resin microspheres.

[0119] (6) The dried phenolic resin microspheres were placed in a tube furnace and subjected to high-temperature carbonization treatment under vacuum (vacuum degree 0.05 kPa). The carbonization temperature was 800 °C, the carbonization holding time was 2 h, and the heating rate was 10 °C / min. After carbonization, the microspheres were cooled to room temperature under vacuum to obtain carbon microspheres.

[0120] Figure 6 This is a scanning electron microscope image of the carbon microspheres prepared in this example. The image shows that the carbon microspheres exhibit a hollow, dense shell structure with a shell thickness of approximately 110 nm and a pore size of less than 2 nm. The microspheres are hollow inside and dense outside. Statistical results indicate that the average particle size of the carbon microspheres is approximately 4 μm (with a particle size range of 2 to 8 μm).

[0121] Comparative Example 1

[0122] This comparative example is used to further illustrate the advantages of the present invention. The specific comparison of the carbon microsphere preparation method is as follows:

[0123] (1) Weigh 180 g of commercially available phenolic resin and 90 g of p-hydroxybenzoic acid and add them to 180 g of ethylene glycol. Stir continuously at room temperature until the phenolic resin and p-hydroxybenzoic acid are completely dissolved to obtain a uniform and transparent precursor solution.

[0124] (2) Weigh 100 g of the precursor solution and add it to 2000 g of phenyl silicone oil. Transfer the resulting mixed solution to a reaction vessel, stir it continuously at 400 r / min, and heat it to 160 °C for 25 min (keep stirring during the heating and holding process). Large pink particles are observed in the solution, indicating that the phenolic resin has been cured.

[0125] (4) The pink large particles were separated by filtration, and the solid product obtained by filtration was collected. The solid product was washed with acetone several times to fully remove the residual phenyl silicone oil.

[0126] (5) The washed solid product was placed in an oven at 120 °C and dried for 5 h to obtain dry large phenolic resin particles.

[0127] (6) The dried phenolic resin large particles were placed in a tube furnace and subjected to high-temperature carbonization treatment under vacuum. The carbonization temperature was 800°C, the carbonization holding time was 2 hours, and the heating rate was 10°C / min. After carbonization, the particles were cooled to room temperature under vacuum to obtain carbon particles.

[0128] Figure 7 This is a scanning electron microscope image of the carbon particles prepared in this comparative example. The image shows that the carbon particles are formed by the bonding and aggregation of a large number of hollow carbon microspheres with an average particle size of about 120 μm. However, the large-sized particles formed by the aggregation of such microspheres are difficult to meet the requirements for the particle size of carbon materials in practical applications. Although ball milling can reduce the particle size, it will destroy the microsphere structure and increase the cost. Compared with the preparation method in Examples 1-6, the key difference of this comparative example is the use of a lower stirring rate and continuous stirring during the curing stage. The lower stirring rate not only causes the size of the microspheres to increase, but also reduces the stability of the emulsion system; while the continuous stirring during the curing process will cause the microspheres to adhere to each other, eventually forming large-sized agglomerated particles.

[0129] Comparative Example 2

[0130] This comparative example is used to further illustrate the advantages of the present invention. The specific comparison of the carbon microsphere preparation method is as follows:

[0131] (1) Weigh 180 g of commercially available phenolic resin and 20 g of hexamethylenetetramine and add them to 180 g of ethylene glycol. Stir continuously at room temperature until the phenolic resin and hexamethylenetetramine are completely dissolved to obtain a uniform and transparent precursor solution.

[0132] (2) Weigh 100 g of the precursor solution and add it to 2000 g of phenyl silicone oil. Emulsify the mixture at room temperature using a high-speed emulsifier at 6000 r / min for 20 min to obtain a stable white alcohol-in-oil emulsion.

[0133] (3) The resulting white emulsion was transferred to a reaction vessel, heated to 160 °C, and kept at this temperature for 24 h. The emulsion was observed to become clear, and yellow lumpy solids were deposited at the bottom of the reaction vessel.

[0134] (4) The yellow solid block was washed with acetone several times to fully remove the residual silicone oil.

[0135] (5) The washed solid product was placed in an oven at 120 °C and dried for 5 h to obtain a dry phenolic resin block.

[0136] (6) The dried phenolic resin block was placed in a tube furnace and subjected to high-temperature carbonization treatment under vacuum. The carbonization temperature was 800°C, the carbonization holding time was 2 h, and the heating rate was 10°C / min. After carbonization, the block was cooled to room temperature under vacuum to obtain a carbon block.

[0137] Figure 8 This is a scanning electron microscope image of the carbon block prepared in this comparative example. The image shows that the carbon block has not formed a microsphere structure and there are a large number of large-sized holes inside. Compared with the preparation method of Examples 1-6, the key difference of this comparative example is the selection of the alkaline catalyst hexamethylenetetramine. Since the curing rate of the alkaline catalyst is significantly lower than that of the acidic catalyst, the precursor droplets in the emulsion are in an uncured liquid state for a long time during the heating stage. These liquid droplets gradually settle and continue to merge at the bottom of the container, eventually forming amorphous large-sized resin blocks.

Claims

1. A method for preparing carbon microspheres, characterized in that: The method comprises the following steps: (1) Preparation of precursor solution: dissolve the resin and acidic catalyst in an alcohol solvent to obtain a precursor solution; (2) Emulsion preparation: the precursor solution obtained in step (1) is added to the oily continuous phase, and emulsified at a stirring speed of 3000-20000 r / min for 1-30 min to prepare an emulsion; (3) Resin curing: heating the emulsion obtained in step (2) at a temperature of 70 to 180°C for a time of 5 min to 1 h; the resin in the emulsion is cured into resin microspheres; (4) Solid-liquid separation; (5) Drying the resin microspheres: washing and drying the solid product after solid-liquid separation in step (4) to obtain dry resin microspheres; (6) High-temperature carbonization: The dry resin microspheres obtained in step (5) are placed in a vacuum or inert atmosphere for high-temperature carbonization to obtain carbon microsphere products.

2. The method for preparing carbon microspheres according to claim 1, wherein: The resin in step (1) is one or more of melamine-formaldehyde resin, phosphorus-modified melamine-formaldehyde resin, boron-modified melamine-formaldehyde resin, sulfur-modified melamine-formaldehyde resin, phenolic resin, boron-modified phenolic resin, silicon-modified phenolic resin, silicon-boron-modified phenolic resin and chitosan-modified phenolic resin; The acidic catalyst is one or more of formic acid, acetic acid, benzoic acid, hydrochloric acid, terephthalic acid, p-hydroxybenzenesulfonic acid, p-toluenesulfonic acid, p-hydroxybenzoic acid and p-toluic acid; The alcohol solvent is one or more of ethylene glycol, glycerol, isopropyl alcohol and n-propyl alcohol.

3. The method for preparing carbon microspheres according to claim 1, wherein: The mass ratio of the resin to the acidic catalyst in step (1) is 200:1 to 1:1; the mass ratio of the alcohol solvent to the resin is 10:1 to 1:

5.

4. The method for preparing carbon microspheres according to claim 1, wherein: The oily continuous phase in step (2) is one or more of dimethyl silicone oil, phenylmethyl silicone oil, epoxy silicone oil, and industrial white oil, and the mass ratio of the oily continuous phase to the precursor solution is 30:1 to 1:

1.

5. The method for preparing carbon microspheres according to claim 1, wherein: The emulsification in step (2) is carried out in a high-speed homogenizer at a stirring speed of 4000-15000 r / min and an emulsification time of 10-30 min.

6. The method for preparing carbon microspheres according to claim 1, wherein: The cleaning solution in step (5) is one or more of solvent oil, benzene, xylene and kerosene; The drying temperature is 60-200° C., and the drying time is 30 minutes to 6 hours.

7. The method for preparing carbon microspheres according to claim 1, wherein: The inert atmosphere in step (6) is one or both of nitrogen and argon, with a gas flow rate of 1 to 10 L / min; the vacuum condition is a vacuum degree of ≤0.1 kPa; The carbonization temperature is 500-1500° C., the carbonization heating rate is 1-10° C. / min, and the carbonization holding time is 1-10 hours.

8. The carbon microspheres prepared according to the method for preparing carbon microspheres according to any one of claims 1 to 7, characterized in that: The carbon microspheres have a particle diameter of 1 to 30 μm and a specific surface area of ​​300 to 700 m 2 / g; A variety of micromorphologies can be formed by controlling the curing temperature and the ratio of resin, acid catalyst and alcohol solvent: When the ratio of resin to acid catalyst is 30:1~10:1, the ratio of alcohol solvent to resin is 3:1~1:2, and the curing temperature is 70~140℃, the carbon microspheres have a shell-free aerogel structure; When the ratio of resin to acid catalyst is 9:1-6:1, the ratio of alcohol solvent to resin is 3:1-1:2, and the curing temperature is 70-140 °C, the carbon microspheres are porous shell-encapsulated aerogel structures. When the ratio of resin to acid catalyst is 5:1-3:1, the ratio of alcohol solvent to resin is 3:1-1:2, and the curing temperature is 70-160 °C, the carbon microspheres are dense shell-encapsulated aerogel structures. When the ratio of resin to acid catalyst is 2:1~1:1, the ratio of alcohol solvent to resin is 10:1~1:2, and the curing temperature is 70~180℃, the carbon microspheres have a hollow dense shell structure. When the ratio of resin to acid catalyst is 30:1~6:1, the ratio of alcohol solvent to resin is 3:1~1:2, and the curing temperature is 160~180℃, the carbon microspheres have an aerogel shell-hollow structure; When the ratio of resin to acid catalyst is 200:1~1:1, the ratio of alcohol solvent to resin is 1:3~1:5, and the curing temperature is 70~180 ℃, the carbon microspheres have a solid structure.

9. Use of the carbon microspheres according to claim 8 as electrode active materials in supercapacitors, characterized in that: The electrode prepared using the carbon microspheres as the electrode active material has a specific capacitance of 200~300 F / g in 6M KOH aqueous solution.

Citation Information

Patent Citations

  • Carbon aerogel microspheres as well as preparation method and application thereof

    CN117923467A